Location, space, and development : development trajectories in India's north east - Indrakumar, Konthoujam; Thangjam, Homen; Centre for Alternative Discourse, Manipur (New Delhi : Published for Centre for Alternative Discourse, Manipur, by Concept Pub. Co., 2011)
Contributed articles
Includes bibliographical references and index
Keywords: Economic development -- India, Northeastern; Industrial location -- India, Northeastern; Space in economics; India, Northeastern -- Economic policy